PROGRAM TRAINING DUTA BAHASA SEBAGAI AGEN PENYULUH BAHASA DAN LITERASI - Muhammad Asyura (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2024)
The Indonesian Study (TBI) of FTIK IAIS Sambas also supports educational programs, especially in efforts to promote literacy in Sambas Regency. One of these programs is manifested in sending delegates to West Kalimantan Language Ambassadors every year which of course requires training and implementation of literacy advocacy for the benefit of the community. The purpose of this community service is to invite language and literature ambassadors through training and program implementation to support community literacy in Sambas Regency. The author uses service learning methods that are in accordance with andragogy (educational theory for adults) which is implemented through public speaking, personal branding, and pageant manner training. The result of the training was 2 delegates to the quarantine stage with one person who won third place. The Language Ambassadors 2024 representing Sambas Regency have contributed by implementing literacy programs in the campus and public. The training program was continued by the IAIS Sambas Quality Assurance Institute (LPM) which was handled and funded directly by the Student Reasoning and Creativity Center.